Dopaminergic Modulation of Prefrontal Cortical Input to Nucleus Accumbens Neurons In Vivo - Brady, Anne Marie (J Neurosci, 2004)
Dopaminergic transmission in the nucleus accumbens has been proposed to modulate the effects of converging excitatory inputs from the cortex, hippocampus, and amygdala. Here, we used in vivo intracellular recording in anesthetized rats to examine the response of nucleus accumbens neurons to stimulation of the prefrontal cortex (PFC) and the ventral tegmental area (VTA). The EPSP elicited in accumbens neurons by PFC stimulation was attenuated by VTA train stimulation in a pattern mimicking dopamine cell burst firing. PFC-elicited EPSPs were smaller in amplitude and faster to decay after VTA stimulation. These changes could not be explained by membrane depolarization alone, because EPSPs evoked during the sustained depolarization after VTA stimulation were significantly smaller than EPSPs evoked during spontaneously occurring up states. Furthermore, no attenuation of PFC-elicited responses was observed during depolarization produced by positive current injection through the recording electrode. Administration of a D(1) antagonist (SCH 23390; 0.5 mg/kg, i.p.) had no effect on the VTA reduction of PFC-elicited responses, whereas administration of a D(2) antagonist (eticlopride; 0.5 mg/kg, i.p.) reversed the reduction of PFC inputs when the analysis was limited to comparisons with spontaneous up states. These results suggest that the ability of PFC inputs to drive accumbens neurons is dampened by dopamine acting primarily at D(2) receptors. Along with previous reports of dopaminergic attenuation of limbic afferents to the accumbens, these findings support the hypothesis that dopamine mediates the selection and integration of excitatory inputs and thus shapes information processing in accumbens output neurons.